Comparison of population genetic estimates amongst wild, F1 and F2 cultured abalone (Haliotis midae). (12th March 2014) - Rhode, Clint; Maduna, Simo N.; Roodt‐Wilding, Rouvay; Bester‐van der Merwe, Aletta E.
Summary Haliotis midae is South Africa's most important aquaculture species. The reproduction cycle is currently not closed as many farms rely on wild‐caught broodstock for seed production. However, there is an increasing interest in genetic improvement in commercial stocks, with a growing number of producers implementing selective breeding strategies. High throughput commercial production and mass spawning make it difficult to maintain breeding records; therefore, mostly mass selection is practised. The high fecundity and unequal parental contributions also often lead to increased levels of inbreeding. This study therefore aimed to assess the genetic effects of such breeding practices on commercial populations of H. midae. Using microsatellite loci, the genetic properties of a wild, an F1 and an F2 population were estimated and compared. Although there was no significant loss of genetic diversity amongst the cultured populations in comparison with the wild progenitor population, there was low‐to‐moderate genetic differentiation between populations. Relatedness amongst the F2 population was significant, and the rate of inbreeding was high. The effective population size for the F2 (±50) was also comparatively small with respect to the wild (∞) and F1 (±470) populations. These results suggest that farms need to give caution to breeding practices beyond the first (F1) generation and aim to increase effective population sizes and minimise inbreeding to ensure long‐term genetic gain and productivity. This study also confirms the usefulness of population genetic analyses for commercial breeding and stock management in the absence of extensive pedigree records.